Enhancing language learning: EFL teachers’ insights on online autonomous learning activities - Ahmed Al Shlowiy; Praveen Raj (Studies in English Language and Education)
Students can improve their skills, broaden their knowledge, and practice their language using online language learning resources. These resources include several activities designed to meet students’ requirements, promote self-learning, and fit their learning preferences. This study investigates EFL teachers’ perceptions of students’ performance in online self-learning activities during laboratory classes. They reflect on how these activities can excite students’ interest, motivate them, and involve them. The research addresses two questions: (a) what teachers think about the importance of e-learning laboratory activities in language learning, and (b) how these activities can promote personalized and active learning. The researchers employed a survey, interviews, field notes, reflections, and class recordings to describe, examine, and interpret the data through narrative analysis. The results show encouraging trends in engagement, motivation, interest, time, independence, and future use. Most students had strong critical thinking skills and enjoyed the self-completion of the assignments. Few learners became demotivated and lost interest owing to the absence of grading, seriousness, or effective surroundings. Additionally, the research shows that compared to traditional face-to-face learning, online learning gives teachers more time and opportunities to update their methods and help students in new ways.